Entertainment: Sing to de-stress - Mahdzar, Mazlina; Yusnizal, Nur Hidayah; Abdul Aziz, Nur Azza; Mohd Shafie, Nur Farisha; Mohd Rakhib, Nur Ainaa Madihah; Che Mohd Fauzi, Mohamad Al-Amin (Multidisciplinary Applied Research and Innovation, 2021)
The use of social media is a tool for professional communication. Sing to de-stress through a social media platform namely Facebook Live streaming is an entertainment programme. This programme will lead spectators to communicate with performers or singers on a real-time basis and mainly can minimize direct interaction with other spectators due to the pandemic Covid-19. The singer can still gain income from their performance rendered through the number of viewers and likes or stars that are given by the audience or from donation drives by the Facebook page. The main reason this idea was created is that there are a lot of street singers who find it hard to gain income due to the Covid-19 pandemic and strict Standard Operating Procedures (SOP), thus this idea was form as way to release the stress during the pandemic of Covid-19 which is through entertainment. Participants and singers alike can reduce their stress during this Covid-19 while joining this kind of entertainment competition using the social media platform.